Pembelajaran Berbasis Nilai-nilai Kebangsaan: Suatu Strategi dalam Menangkal Radikalisme di Persekolahan - Fahmi, Rizal (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2020)
The purpose of this research is to investigate the implementation and impact the program of the ToT Nilai-nilai Kebangsaan Lemhannas RI for teachers and lecturers in West Java Province. Some previous researches explained that radicalism growth in the world of schooling in West Java. From the internalization of national values carried out by teachers towards students, it was formed as an effective strategy as well as a model of deradicalization in schooling. This research was conducted using a qualitative approach. Interviews and observations were chosen as data collection techniques to obtain deep results. The results of this research were that the teachers who were alumni of the ToT Nilai-nilai Kebangsaan Lemhannas RI generally participate in socializing national values in learning through varied methods in accordance with the subjects they are taught. There were differences way or method in implementing nilai-nilai kebangsaan into the course, even though student’s respond was enthusiast.